Perancangan Sistem Tes Pengukuran Fisik Atlet PPLP Berbasis Android Pada Asisten Deputi Pengelolaan Pembinaan Sentra dan Sekolah Khusus Olahraga - Miswan, Miswan (Jurnal Ilmu Komputer, 2023)
The Android-based physical measurement system for PPLP athletes under the Assistant Deputy for Management of Development Centers and Special Sports Schools was created to make it easier for coaches and test officers to take physical measurements of PPLP athletes. Currently, the measurement process is still carried out manually using paper and data processing via Microsoft Excel, which is then sent via email, resulting in delays in receiving data by the central government. Previously, there had been similar research using Android to measure physical conditions with case studies and different test instruments, so the researchers chose to use this platform to overcome the problems in this case study. This system will use the Android programming language and MySQL database, with implementation stages using UML. The system development method applied is SDLC with a waterfall model. Black box testing is carried out during the process of inputting physical test data to ensure application performance. The test results fulfill the needs of the Assistant Deputy for Management of Special Sports Centers and Schools, namely providing accurate and fast physical measurement test results for PPLP athletes to the Central Government.